Strategi Pemasaran Kreatif UMKM Kuliner melalui TikTok untuk Menarik Minat Beli Gen Z di Kota Medan - Poniman, Poniman; Renaldi, Refli; Harahap, Sandhi Fialy (Jurnal Ilmiah Poli Bisnis, 2025)
This study aims to analyze the effectiveness of using TikTok as a digital marketing platform by MSMEs in Medan to attract the purchasing interest of Generation Z. Using a quantitative approach and the UTAUT2 model, this study identifies five operational variables: Performance Expectancy, Hedonic Motivation, Perceived Trust, Behavioral Intention, and Actual Behavior. Data was collected from 100 respondents, who are TikTok users and part of Generation Z. The results show that Performance Expectancy and Hedonic Motivation significantly influence Perceived Trust and Behavioral Intention. Furthermore, Behavioral Intention significantly impacts Actual Behavior in the context of purchase decisions. This study provides insights into how MSMEs in the culinary sector can leverage TikTok to strengthen their marketing strategies and attract the attention of Gen Z consumers in Medan.